The effects of micronutrient-enriched media on the efficacy of Bacillus subtilis as biological control agent against Meloidogyne incognita - Muh. Adiwena; Aditya Murtilaksono; Saat Egra; Mohammad Hoesain; Iis Nur Asyiah; Ankardiansyah Pandu Pradana; Zidna Nurul Izatika (Biodiversitas Journal of Biological Diversity, 2023)
The root-knot nematodes Meloidogyne incognita poses a serious threat to horticultural food and plantation crops. One of the effective and efficient measures to overcome this nematode is using bacteria as a biological control agent. This study aimed to test the effectiveness of Bacillus subtilis bacteria grown on media with additional micronutrients as a biological control agent for M. incognita. The test was carried out by growing bacteria in 100 mL of nutrient broth (NB) added with FeCl2, MnCl2, and CuCl2. Each type of micronutrient was administered at concentrations of 35 ppm, 40 ppm, 45 ppm, 50 ppm, and 55 ppm. As a control, NB media was used without the addition of micronutrients. The test results showed that the best performances on bacterial growth were 55 ppm MnCl2, 45 ppm MnCl2, 40 ppm MnCl2, 40 ppm CuCl2, 50 ppm MnCl2, and 35 ppm MnCl2. These six treatments were then used in an antagonism test. A total of 150 J2 M. incognita in 4 mL of suspension was put into a petri dish with a diameter of 5 cm. After that, 1 mL of each bacterial suspension was put into a petri dish following the treatment. The mortality rate of M. incognita in each treatment was 77.5% in 55 ppm MnCl2, 74.5% in 45 ppm MnCl2, 77.25% in 40 ppm MnCl2, 73.25% in 40 ppm CuCl2, 78.75% in 50 ppm MnCl2, 79% in 35 ppm MnCl2, and 53.25% in control. The same six treatments were also used to measure the chemotaxis index of M. incognita on tomato roots. Tomato seeds of the Tantyna variety were soaked for 60 minutes in a bacterial suspension grown on micronutrient-enriched media. After seven days, the tomato seed roots were removed and placed in 5 mL 20% Pluronic F-127 Gel which had been infested with 100 J2 M. incognita. After 6 hours, the number of nematodes approaching the roots was observed. The chemotaxis index in the treatments ranged from 16% to 24%, while that in the control was 33%. This study corroborates that the addition of micronutrients MnCl2 and CuCl2 to the growth medium of B. subtilis can increase antagonistic activity against M. incognita and suppress its chemotaxis response in tomato roots soaked in the bacterial suspension.